Implementation of the Amtsilati Method in Improving the Reading Ability of Santri's Yellow Books - Al Abror, M. Abdul Malik; Hernisawati, Hernisawati; Wijaya, Adi (International Journal on Advanced Science, Education, and Religion, 2025)
This study aims to analyze the implementation of the Amtsilati method in improving the reading skills of yellow books of students at the Al Falahiyah Islamic Boarding School, Batanghari, East Lampung. The approach used in this study is a qualitative method with data collection techniques through observation, interviews, and documentation. The analysis was carried out using data reduction techniques, data presentation, and verification of findings based on triangulation of sources and methods. The results of the study indicate that the Amtsilati method is effective in improving students' understanding of Nahwu & Shorof. This method provides a more systematic learning structure, makes it easier for students to memorize Arabic language rules, and improves their skills in reading and understanding yellow books independently. However, this study also found that the main challenges in implementing this method are the limited resources of competent teachers and the lack of consistency of students in practicing the material that has been learned. Thus, this study recommends strengthening learning strategies based on the Amtsilati method with a more interactive and adaptive approach, as well as improving the quality of teachers to support the effectiveness of this method in the long term).